Editorial - Oniwide, Oyetola (NIU Journal of Social Sciences; Vol 11 No 4 (2025): NIU Journal of Social Sciences, Vol. 11 No. 4, December 2025, 2025)
This edition of NIU Journal of Social Sciences focuses on Development Administration, Social Philosophy and Organizational or Personnel Management. The first part of the Journal addresses issues in Development Administration such as Rural Farming, Anti-Corruption Policies, National Security, Civil-Military Cooperation, Government Empowerment and Decentralization in Development Decision-Making. It is argued in one of the papers that meaningful decentralization is essential for sustainable development and democratic consolidation in Nigeria. It is therefore, suggested amongst others, that Federal government must enforce the 2024 Supreme Court judgment, initiate constitutional amendments, establish support programs, and strengthen monitoring. State governments must respect local autonomy, conduct credible elections, support capacity building, and enable revenue generation. Papers in the second section are on Social Philosophy. One of the papers in this Section explores how parental income, education, and family structure influences youth behaviour, propensity and predisposition to internet crime. Anchored on Relative Deprivation Theory, the study finds that although youths engage in internet crime, socio-economic conditions and family dysfunction are an indirectly influence that shapes such behavioural tendencies while pointing that deprivation and societal glorification of wealth act as motivating factors. The paper concludes that addressing youth unemployment, improving parenting quality, and reshaping societal values are crucial in mitigating internet crime.   In last section on Organizational and Personnel Management, one of the papers explores the effects of leader-member exchange, job satisfaction and motivation on organizational commitment in public service with major focus on National Examinations Council Offices in Nigerian North-Central States of Niger, Benue and Nasarawa. These findings of the paper highlight the importance of positive leader-member relationships, meaningful job roles, and both intrinsic and extrinsic motivation in fostering strong organizational commitment. Specifically, the paper suggests that the agency must invest in recognition programs, employee empowerment, improved health and safety provisions, and clearer leader–employee communication pathways in order to strengthen commitment. This is because enhancing these job satisfaction dimensions is likely to yield a more motivated, committed, and productive workforce. On the whole, this issue of NIU Journal of Social Sciences features many interesting research papers. Some of these papers are empirical in nature while others have theoretical base. Each of them focuses on one specific social and management problem or the other; trying to proffer solutions to them. Readers are therefore advised to make proper use of the ideas presented by the various authors.